2019
DOI: 10.1111/ene.13907
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent ischaemic cerebrovascular events as presenting manifestations of myeloproliferative neoplasms

Abstract: Background and purpose Myeloproliferative neoplasms (MPNs) – polycythemia vera, essential thrombocythemia and primary myelofibrosis – are associated with increased risk for ischaemic cerebrovascular events (ICVEs). Due to their low prevalence, MPNs often remain undiagnosed as the cause of ICVEs. Methods Case records at the University of Tübingen between 2014 and 2017 were screened to identify patients with MPN‐related ICVEs. Clinical features, brain imaging, laboratory findings, applied treatments and neurolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…[10][11][12] Of the 26 studies in the meta-analyses, only four included non-IS, in proportions of 6.2-15.8%. [15][16][17][18] The meta-analyses included a total of 46,633 individuals with stroke (per study: median, 1,132; IQR: 407-3,069), of which about 0.5% (n ¼ 226) were nonischemic.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…[10][11][12] Of the 26 studies in the meta-analyses, only four included non-IS, in proportions of 6.2-15.8%. [15][16][17][18] The meta-analyses included a total of 46,633 individuals with stroke (per study: median, 1,132; IQR: 407-3,069), of which about 0.5% (n ¼ 226) were nonischemic.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…As MPN are relatively rare, it is probable they represent an underdiagnosed cause of cerebral thrombosis. High 2 Case Reports in Hematology clinical awareness is warranted to identify an underlying MPN in order that a prompt treatment is initiated (e.g., antiplatelet, cytoreductive, and phlebotomy) [24,25]. While some studies have suggested routine screening for JAK2 V617F in patients presenting with stroke and/or cerebral venous thrombosis (CVT) [26], given the lower risk of thrombosis in CALR-and MPL-mutated MPN patients and the near absence of these mutations in CVT cohorts [27,28], wider evaluation of mutation status might be reserved for those patients with sustained abnormal blood count findings.…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective study, among 3318 patients with ischemic vascular cerebral events, 17 (0.5%) were diagnosed with MPN, and stroke was the revealing manifestation for 58% of them. 1 Moreover, 29% of these patients had a history of repeated ischemic cerebral event preceding the diagnosis of MPN. Nevertheless, in this large cohort, another associated cause existed in all these stroke patients with MPN.…”
Section: Characteristics Of Arterial Stroke In Myeloproliferative Neoplasms: a French Monocentric Studymentioning
confidence: 99%
“…Nevertheless, in this large cohort, another associated cause existed in all these stroke patients with MPN. 1 In the emergency setting of a stroke, diagnosing underlying MPN can be difficult. First, MPN patients share common cardiovascular comorbidities that affects stroke risk in the same way than it does in general population.…”
Section: Characteristics Of Arterial Stroke In Myeloproliferative Neoplasms: a French Monocentric Studymentioning
confidence: 99%
See 1 more Smart Citation